2017
DOI: 10.1017/s1092852917000116
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the DSM–5 and ICD–10: panic and other anxiety disorders

Abstract: Anxiety disorders are the most prevalent mental disorders and are associated with substantial healthcare costs and a high burden of disease. In this article, changes in the new Diagnostic and Statistical Manual for Mental Disorders (the DSM-5) with respect to panic disorder/agoraphobia, generalized anxiety disorder, social anxiety disorder, specific phobias, and selective mutism are compared with the International Classification of Diseases (ICD-10) system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 6 publications
0
9
0
2
Order By: Relevance
“…: fobie specyficzne, zaburzenie lęku separacyjnego, mutyzm selektywny, specyficzna fobia, fobia społeczna, agorafobia, zaburzenie paniczne oraz i uogólnione zaburzenie lękowe); zaburzenia obsesyjno-kompulsywne i zaburzenia z nimi powiązane oraz zaburzenia urazowe i związane ze stresem (między innymi: PTSD -Posttraumatic Stress Disorder) [1]. Grupa zaburzeń lękowych została rozszerzona o zaburzenie lęku separacyjnego, poprzednia wersja DSM sugerowała, iż zaburzenie to dotyczy tylko dzieci [2,3]. Zmiana została wprowadzona uwzględniając wyniki badań epidemiologicznych, które wyraźnie wykazały nieoczekiwanie wysoką częstotliwość występowania zaburzeń lęku separacyjnego u osób dorosłych [4].…”
Section: Wstępunclassified
See 1 more Smart Citation
“…: fobie specyficzne, zaburzenie lęku separacyjnego, mutyzm selektywny, specyficzna fobia, fobia społeczna, agorafobia, zaburzenie paniczne oraz i uogólnione zaburzenie lękowe); zaburzenia obsesyjno-kompulsywne i zaburzenia z nimi powiązane oraz zaburzenia urazowe i związane ze stresem (między innymi: PTSD -Posttraumatic Stress Disorder) [1]. Grupa zaburzeń lękowych została rozszerzona o zaburzenie lęku separacyjnego, poprzednia wersja DSM sugerowała, iż zaburzenie to dotyczy tylko dzieci [2,3]. Zmiana została wprowadzona uwzględniając wyniki badań epidemiologicznych, które wyraźnie wykazały nieoczekiwanie wysoką częstotliwość występowania zaburzeń lęku separacyjnego u osób dorosłych [4].…”
Section: Wstępunclassified
“…specific phobias, separation anxiety disorder, selective mutism, social phobia, agoraphobia, panic disorder, and generalized anxiety disorder); obsessive-compulsive disorders and the related disorders, and trauma and stressor-related disorders (including PTSD -Posttraumatic Stress Disorder) [1]. Separation anxiety disorder was added to the group of anxiety disorders, while the previous version of DSM suggested that this disorder only affected children [2,3]. This change was introduced following the consideration of the results of epidemiological studies which clearly demonstrated an unexpectedly high incidence of separation anxiety disorders in adults [4].…”
Section: Introductionmentioning
confidence: 99%
“…This study examined the effect of the more stringent criterion A in DSM-5 (endorsement of fears from multiple distinct situational domains) on the prevalence rate of AG in children and adolescents seeking anxiety treatment (Cornacchio, Chou, Sacks, Pincus, & Comer, 2015). Whether and how the changes in DSM-5 criteria will affect clinical treatment is yet unclear (Bandelow, 2017); however, additional research into DSM-5 AG in general (Wittchen et al, 2010), and specifically the treatment of DSM-5 AG without PD or panic attacks is warranted, especially given the high persistence of DSM-5 AG shown in the current study. Whether and how the changes in DSM-5 criteria will affect clinical treatment is yet unclear (Bandelow, 2017); however, additional research into DSM-5 AG in general (Wittchen et al, 2010), and specifically the treatment of DSM-5 AG without PD or panic attacks is warranted, especially given the high persistence of DSM-5 AG shown in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…By examining multivariate comorbidity patterns of PD and AG, the authors showed that AG could be categorized as a fear disorder, whereas PD is more strongly related to distress disorders, such as depression (Greene & Eaton, 2016). Yet, evidence is lacking for specific genetic underpinnings of AG (Wittchen et al, 2010) and for differential treatment effects; the latter may result from a lack of treatment studies focusing on patients with AG without PD (Bandelow, 2017;Wittchen et al, 2010). To our knowledge only one other study examined the effect of changes from DSM-IV to DSM-5 criteria for AG.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation